2019
DOI: 10.1029/2019wr025195
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Scale Investigation of Methane Hydrate Dissociation Using the Lattice Boltzmann Method

Abstract: Fundamental understanding of pore‐scale methane hydrate dissociation in porous media is important to evaluate submarine slope stability and potential utilization of methane resources. In this paper, a general pore‐scale framework based on the lattice Boltzmann (LB) method is established for reactive transport coupled with nonisothermal multiple physicochemical processes in porous media. The framework combines the gas hydrate dissociation kinetic model, the single‐phase flow LB model, the mass transport LB mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 78 publications
(125 reference statements)
0
25
0
Order By: Relevance
“…Gas hydrate (i.e., methane) is a complex multi-component and multi-phase fluid flow process accompanied by mass transport and heat transfer in porous media [ 81 ]. One method that can be implemented to analyze that process is LBM [ 31 , 61 ]. Due to its attractive advantages, such as simplicity in coding, dealing with complex solid boundaries, and parallelization, LBM has become a very popular CFD method in many fields, such as multi-phase and multi-component flow, reactive flow, microscale, and nanoscale flow [ 66 , 84 ].…”
Section: Modeling Regarding Dissociation and Formation Of Gas Hydratementioning
confidence: 99%
See 2 more Smart Citations
“…Gas hydrate (i.e., methane) is a complex multi-component and multi-phase fluid flow process accompanied by mass transport and heat transfer in porous media [ 81 ]. One method that can be implemented to analyze that process is LBM [ 31 , 61 ]. Due to its attractive advantages, such as simplicity in coding, dealing with complex solid boundaries, and parallelization, LBM has become a very popular CFD method in many fields, such as multi-phase and multi-component flow, reactive flow, microscale, and nanoscale flow [ 66 , 84 ].…”
Section: Modeling Regarding Dissociation and Formation Of Gas Hydratementioning
confidence: 99%
“…Hence, the mean size and the deviation as distribution factors are crucial parameters for the blockage. Zhang, Zhang [ 31 ] used LBM by combining the gas hydrate dissociation kinetic model, the single-phase flow LB model, the mass transport LB model, and the conjugate heat transfer LB model. The results showed that the simulation using LBM could easily evaluate the reactive transport framework effect to the coupled physicochemical thermal process and provide an understanding of the methane dissociation process at the pore scale.…”
Section: Modeling Regarding Dissociation and Formation Of Gas Hydratementioning
confidence: 99%
See 1 more Smart Citation
“…LBM is a computational fluid dynamics solver based on mesoscopic kinetic equations, which could be utilized to study fluid flow problems (Krüger et al, 2017). LBM has proven to be a powerful tool for solving problems at different length and time scales owing to its advantages in numerical simulation of single‐phase and multiphase fluid flows in pore scale (Bakhshian et al, 2019; Chen et al, 2019; Norouzi et al 2019; Zhang et al, 2019), particularly in complex geometries such as porous media (Bakhshian & Sahimi, 2016; Vasheghani Farahani et al, 2019; Vora & Dugan, 2019). Free‐energy LBM as an option for simulating multiphase and multicomponent fluid flow is able to appropriately account for fluid‐fluid interfacial tensions and solid surface contact angles.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…This is attributed to its attractive advantages, like its general kinetic foundation, high parallelism, and ability to handle multiphysics and complex boundaries [33,34]. Recently, LB models have been proposed to simulate flows of reactive fluids in porous media, like methane hydrate dissolution [35], solid coke combustion [32], and reactive mixing with viscous fingering [36]. Although these works showed the superior ability of the LB method in modeling porous media flows, some limitations should be noted.…”
Section: Introductionmentioning
confidence: 99%